Gen Z' Halal Cosmetic Purchasing: Merely a Way of Life? - Akfini Farihah Fiddarayni; Sepky Mardian (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2022)
Generation Z (Gen Z) have distinctive consumer behavior as trends massively influence them. This study aims to determine the effect of financial literacy, halal certification, and halal awareness of halal-labelled cosmetics among Gen Zs, using the case of undergraduate students in Depok. The methodology used is quantitative with a causal approach. The data were obtained from 101 female students filling out the questionnaire. The data was processed using Partial Least Squares-Structural Equation Model (PLS-SEM). The findings indicated that financial literacy influenced the users of halal cosmetics. However, halal variables related to halal certification and awareness have not significantly influenced cosmetic consumption.